Seguridad Ciudadana El Desempleo Juvenil y su Influencia en la Seguridad Ciudadana: Análisis del Distrito de Carabayllo 2021 - Caro Ybarra, Jorge Elisban Martin (2024)
The present research was aimed at determining whether youth unemployment influences citizen security in the district of Carabayllo in 2021, because there is a problematic situation in that district that had been surpassed by crime, so its security levels citizens are very deficient. To carry out the research, different statistical and data collection tools were used from primary sources of information, such as questionnaires and interviews, as well as obtaining data through the use of secondary sources. Data from primary sources were obtained from 384 people surveyed, of which 50% were young people from the Carabayllo district between 18 and 24 years of age and adults from 25 years of age and older of both sexes and residents of the Carabayllo district, having been interviewed regarding the factors of educational level, unemployment, juvenile delinquency and on the insertion into the labor market of young Venezuelans and how these factors influence citizen security in the Carabayllo district, having determined that these factors constitute very important variables to determine the level of citizen security of the district. The research concluded that the educational level constitutes one of the most important factors to influence citizen security; Likewise, it was possible to determine the need to generate strategies that help strengthen this factor, having presented within the proposal a strategy to generate the development of youth in the district of Carabayllo, which should be the responsibility of the local, regional and national for its implementation, in order to achieve the desired results, which has been expressed in the research recommendations.